Molecular Epidemiology of Mycobacterium tuberculosis in the United States–Affiliated Pacific Islands. (January 2014) - Bamrah, Sapna; Desmond, Edward; Ghosh, Smita; France, Anne Marie; Kammerer, J. Steve; Cowan, Lauren S.; Heetderks, Andrew; Forbes, Alstead; Moonan, Patrick K.
The United States–Affiliated Pacific Islands (USAPI) are part of the US National Tuberculosis (TB) Surveillance System and use laboratory services contracted through a cooperative agreement with the Centers for Disease Control and Prevention (CDC). In 2004, the CDC established the National Tuberculosis Genotyping Service, a system to genotype 1 isolate from each culture-confirmed case of TB. To describe the molecular epidemiology of TB in the region, we examined all Mycobacterium tuberculosis isolates submitted for genotyping from January 1, 2004, to December 31, 2008. Over this time period, the USAPI jurisdictions reported 1339 verified TB cases to the National Tuberculosis Surveillance System. Among 419 (31%) reported culture-confirmed TB cases, 352 (84%) had complete genotype results. Routine TB genotyping allowed, for the first time, an exploration of the molecular epidemiology of TB in the USAPI.